Motivational Differences in Feedback-Seeking Intentions: A Cultural Analysis - MacDonald, Heather Anne (University of Waterloo, 2008)
Two studies examined cultural differences in the propensity to seek performance feedback using an experimental policy-capturing design. Findings demonstrated differences between European-Canadians and Chinese participants in the importance of contextual and individual variables in predicting feedback-seeking intentions. In particular, European-Canadians were more motivated than Chinese participants to seek individual feedback when it was positive versus negative (feedback valence). Further, the ego-based motive (ego-defensiveness) predicted the relationship between feedback valence and feedback-seeking intentions for European-Canadians, whereas the motive did not predict the relationship for Chinese participants. Results indicated that both European-Canadians and Chinese participants were less likely to seek feedback when feedback seeking occurred in public versus private. This finding was qualified by a significant interaction between culture and the image-based motive (defensive impression management) in predicting the relationship between publicness of feedback seeking and feedback-seeking intentions. Specifically, the image-based motive predicted the relationship between the publicness of feedback seeking and feedback-seeking intentions for Chinese participants but did not predict this relationship for European-Canadians. Findings also revealed cultural differences in the propensity to seek feedback from different sources. European-Canadians were significantly more likely than Chinese participants to seek feedback when it came from a supervisor versus a peer. Contrary to prediction, the relationship between the mean beta weight for the Source cue was not predicted by the instrumental motive for European-Canadians. In support of prediction, power distance predicted the relationship between feedback source and feedback-seeking intentions for Chinese participants. Overall, the two studies provide evidence for differences in the motivation to seek feedback between East Asian and Western individuals. Study limitations and future research directions are discussed, as well as practical and theoretical implications of the current findings.
Keywords: culture; work motivation; feedback seeking; Psychology